KAJIAN PENGARUH PENAMBAHAN BORE PILE PADA ABUTMENT TERHADAP KAPASITAS DAYA DUKUNG JEMBATAN (Studi Kasus Abutment 1 Jembatan XYZ): KAJIAN PENGARUH PENAMBAHAN BORE PILE PADA ABUTMENT TERHADAP KAPASITAS DAYA DUKUNG JEMBATAN (Studi Kasus Abutment 1 Jembatan XYZ) - Junaidi; Supriyadi; Az-Zahra, Cintara Viera; Amanda, Vannia Ardelia (Politeknik Negeri Semarang, 2025)
This study discusses the addition of a drill pile foundation on the abutment of the XYZ Bridge. The study aims to analyze the increased structural support capacity of the abutment bridge and provide insights related to the causes of the addition of Bore Pile as well as learning in designing and solving problems on the bridge structure. The research used quantitative methods using secondary data, then calculated the battery supporting power capacity using Mayerhoff and Resse and Wright calculations. Based on the results of the calculation of pile bore addition on abutment 1 has improved the structural support strength of the bridge. This result is demonstrated by comparing the ultimate support power of the group of poles before and after the addition of piles bore which shows a significant increase in the capacity of ultimate supportive power, i.e. before the 14796,08 kN pile boor addition to 303394,60 kN after the addition of piles bore